Analysis of The Morphological Characteristics of Bush Frog Philautus spp. Gistel, 1848 (Anura: Rhacophoridae) from Mount Ungaran - Margareta Rahayuningsih; Winda Rahmawati; Amir Hamidy (Biosaintifika: Journal of Biology & Biology Education, 2021)
Traditionally, the genus Philautus Gistel, 1848 contains small Rhacoporid frogs that lack vomerine teeth and a direct development tadpole stage. In Java, this genus consists of 3 species, including Philautus aurifasciatus, Philautus jacobsoni, and Philautus pallidipes. It is known that Philautus aurifasciatus and Philautus jacobsoni are sympatric species from Mount Ungaran and are morphologically difficult to distinguish. Therefore, information is needed through the phenetic characters of each population in the area to identify differences in their morphology. This study aimed to analyze the morphological characteristics of  Bush Frog Philautus spp. on Mount Ungaran in terms of meristic character through a direct field survey and comparison methods. Furthermore, it was conducted by observing 32 specimens of Philautus spp. from Mount Ungaran and compared with the Philautus aurifasciatus from Mount Gede Pangrango with 18 meristic characters. The results showed that Philautus spp. is similar to Philautus aurifasciatus in terms of their meristic characters. The results of the meristic analysis showed that Philautus spp. has a variety of dorsal colors from brown, purple, green, and gray with two types of patterns including patterned groups (resembling letters H, X, and V) and abstract. Furthermore, the throat, stomach, and lower thighs are granular with three snout shapes (protruding, round, and sloping). It has a loreal oblique tympanum and canthus rostralis. The forelimbs are not webbed while the hindlimbs are half webbed, and the inner metatarsal is an elongated oval in shape. Meristic analysis provides a basis for strengthening the taxonomic status of Philautus spp on Mount Ungaran, as well as information the distribution in Mount Ungaran.